Listeners’ Linguistic Experience Affects the Degree of Perceived Nativeness of First Language Pronunciation - Kornder, Lisa; Mennen, Ineke (Frontiers in Psychology, 2021)
The aim of this study was to explore if and to what extent Austrian-English late sequential bilinguals who have been living in a second language (L2) environment for several decades are perceived to sound native in their first language (L1) when being compared to monolingual Austrian German control speakers. Furthermore, this investigation aimed to identify if listeners differ in their judgments of nativeness of L1 pronunciation depending on their own language background. For this purpose, two groups of native Austrian German listeners (N = 30 each), who differed regarding their linguistic background (Austrian German monolingual and Austrian German-English bilingual listeners) were asked to rate spontaneous speech samples produced by Austrian English bilingual and Austrian German monolingual speakers. Results showed that the bilingual L1 speech was perceived to sound overall less native compared to monolingual control speech. It was further observed that the two listener groups significantly differed in their perception of nativeness: Bilingual listeners were overall less likely to judge bilingual L1 pronunciation to sound non-native compared to monolingual listeners. To date, this is the first study to show that listener experience influences their perception of nativeness of L1 pronunciation and, thus, adds a new dimension to the notion of the native speaker.